2019
DOI: 10.1016/j.measurement.2018.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Development of low cost packaged fibre optic sensors for use in reinforced concrete structures

Abstract: There is an ongoing need to measure strains in reinforced concrete structures more reliably and under a range of circumstances e.g. long term durability (such as effects of cracking and reinforcement corrosion), response to normal working loads and response under abnormal load conditions. Fibre optic sensors have considerable potential for this purpose and have the additional advantages, including of immunity to electromagnetic interference and light weight (Grattan et al, 2000). This is important in railway s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 11 publications
0
8
0
2
Order By: Relevance
“…Scott et al [ 29 ] developed a cost-effective and easy-to-use technique for encapsulating resin fiber optic sensors, using a 3D printing technique sensor system suitable for use with concrete structures for both surface mounting and embedment situations. Tests performed by the authors demonstrated the potential of the packaged sensors for strain measurement in concrete structures, but further development is still needed to assess the quality of their applicability.…”
Section: Overview Of Health Monitoring Of Concrete Structures Using Fosmentioning
confidence: 99%
See 1 more Smart Citation
“…Scott et al [ 29 ] developed a cost-effective and easy-to-use technique for encapsulating resin fiber optic sensors, using a 3D printing technique sensor system suitable for use with concrete structures for both surface mounting and embedment situations. Tests performed by the authors demonstrated the potential of the packaged sensors for strain measurement in concrete structures, but further development is still needed to assess the quality of their applicability.…”
Section: Overview Of Health Monitoring Of Concrete Structures Using Fosmentioning
confidence: 99%
“…Another research that used FOS to read concrete strains was developed by Sienko et al [ 29 ]. In this work, fiber optic sensors were used to investigate strains and cracks in a reinforced concrete element during a load test.…”
Section: Overview Of Health Monitoring Of Concrete Structures Using Fosmentioning
confidence: 99%
“…The ingress movement of chloride ions in RCC structures is calculated using Fick's second law of diffusion, as shown in Equation (1). This is mostly used when designing the service life of structures located in a marine environment [16].…”
Section: Introductionmentioning
confidence: 99%
“…Reinforced concrete (RC) structures are known for their longevity and resistance, which are very valuable in civil engineering practices [ 1 ]. This includes the construction of harbor docks, marine structures, and coastal roads.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber Optic Sensors (FOSs), on the other hand, have considerable potential for this purpose and have additional advantages, such as, immunity to electromagnetic interference and their light weight [ 19 ]. This is an important aspect for some civil infrastructure, i.e., railways where the lines are electrified [ 20 ]. Thus, there has been in depth research on the feasibility and deployment of FOSs for SHM purposes [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%